Plasmid profile determination of Escherichia coli and Klebsiella pneumoniae producers of extended spectrum ß-lactamase isolated in urocultives - Suarez, Carlos (2018)
Introduction. The increase in resistance rates in uropathogenic bacteria and their spread has become in a significant worldwide public health, becoming more important the spread of resistant isolates producing of extended spectrum ß-lactamases, which are useful the molecular characterization of plasmids and other genetic elements of the bacteria to establish the genetic relationship between them, to have relevant data that we can suggest the direction of propagation of this type of resistance. The object of research was to determine the plasmid profiles in isolates of Escherichia coli and Klebsiella pneumoniae producing of extended spectrum ß-lactamases from urine cultures of the National Institute of Child Health, Lima, Peru. Methods. Descriptive, observational cross-sectional study. Results. Were detected different electrophoretic patternsin the samples, obtained from 1-7 bands per sample and a total of 15 bands of different sizes, which varied from 1.5 kb to more than 20 kb. Considering the fingerprint patterns, the isolates analyzed were distributed into different clusters or branches, using the NTSYSpc 2.1 program and the UPGMA clustering algorithm. Conclusions. No genetic similarity was found between isolates of community origin and of origin associated with health care, so it is not possible to establish a meaningful relationship and to determine a common origin among them.